Aktualne aspekty teorii pieniądza G. F. Knappa - Knakiewicz, Zenobia (Wydział Prawa i Administracji UAM, 1984)
The monetary theory of G. F. Knapp was so shocking in the moment of its announcement that it was rejected. Yet, demonetarization of gold is presently materialized and the authoress made an attempt at the study of that theory. Her task was to present main theses of G. F. Knapp and to examine whether the theory found its application in the modern monetary systems. Upon presentation of main theses of G. F. Knapp references were made to the theories of John Law, L. Walras. J. M. Keynes. The differences between metalism and nominalism were indicated. In the answer to the query the immediate interest of G. F. Knapp theses was emphasised. Applications of his theory in current international monetary system is brought forward. It was proved by G. F. Knapp that money is always an autonomous tender. Moneyed function is its, essence. Money is always numéraire. Substantional value od money is unnecessary and so are gold parity and par value system. State can fix a nominal value of its currency, as a compulsory legal tender and secure a future purchasing power as means of exchange. The exchange rate is a price of foreign currency expressed in a domestic unit. In cannot be fixed arbitrarily, as it is formed by the whole of state policies and international exchange. According to the Knappian pantopolical theory of exchange rate, a state has to run the monetary policy both inland and with reference to the foreign relations. All fundamental Knappian theses are presently fully realised in monetary system of many countries. In the international monetary system it is used in basket currency introduced by the IMF in 1974 as well as in establishing principles of central rate.
Current aspects of the monetary theory of G. F. Knapp